Learning from Experience: Case Studies of Area-based Planning in ABNJ - United Nations Environment Programme World Conservation Monitoring Centre (2022)
This study has been undertaken as part of the Food and Agriculture Organization of the United Nations (FAO) and United Nations Environment Programme (UN Environment) jointly implemented Global Environment Facility (GEF) funded project entitled ‘Sustainable fisheries management and biodiversity conservation of deep-sea living resources and ecosystems in Areas Beyond National Jurisdiction, known as the ABNJ Deep Seas Project. Recognising the importance of healthy, fully functioning marine ecosystems for marine biodiversity, food security, economic prosperity and sustainable livelihoods is a key pillar of the Areas Beyond National Jurisdiction Deep Seas Project. As a result, a number of analyses have been undertaken to inform the development of a methodology to support application of cross-sectoral area-based planning in areas beyond national jurisdiction by parties to Regional Seas Conventions and their Secretariat. This report constitutes one such analysis and explores four case study regions in which area-based planning has occurred in areas beyond national jurisdiction: ❚ Eastern Central (EC) Pacific; ❚ Mediterranean; ❚ North East (NE) Atlantic; and ❚ Southern Ocean. The four case study regions demonstrate a variety of different contexts and methods for area-based planning in areas beyond national jurisdiction. Case study regions were identified based on the existence of advanced area-based planning tools and evidence of cross-sectoral coordination to undertake area-based planning.